(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
The essay provides a reflection on the current polycrisis focused on urban spaces, analyzing the novel Valpore by the Chilean writer Cristóbal Gaete. The novel fictionalizes the city of Valparaíso through a narrative proposal that radicalizes its historical associations with marginality, debauchery, and catastrophe. Taking these imaginaries to the extreme, Valpore develops a poetic of destruction, accusing the failure of the tourist-patrimonial model of the city as the main promoter of social exclusion and uncontrollable violence in Valparaíso. The novel uses a destructive aesthetic to attack the values that underpin common sense, highlighting the need to rethink our set of beliefs with which we unsuccessfully try to address the current problems. The conclusions of the essay warn about the possible alternatives to the catastrophic state of Valparaíso that could be explored in the novel. One of them is to suspend the practical imperative of taking action to try to address the polycrisis. Instead, the novel proposes stopping, doing nothing, sitting, and waiting, as the narrator does at the end of the story. This is a way of making the unthinkable and the radically different emerge, to begin to imagine a truly different future.